Cerebrovascular accumulation of amyloid‐forming amylin secreted from the pancreas induces brain hypoxia. (20th December 2022) - Verma, Nirmal; Ly, Han; Despa, Florin
Abstract: Background: Islet amyloid polypeptide (amylin) is a β‐cell hormone co‐secreted with insulin. Histological analyses of human brains identified amylin deposits co‐localized with parenchymal and vascular β‐amyloid in humans with vascular cognitive impairment and Alzheimer's dementia. Because circulating amyloid‐forming amylin triggers systemic hypoxia signaling, we sought to determine the relationship between circulating amylin levels and brain hypoxia markers in a transgenic rat model of amylin‐mediated neurological deficits. Method: To assess amylin‐related brain hypoxia signaling, we performed a 16‐month longitudinal study in which rats that express amyloid‐forming human amylin in pancreatic β‐cells (HIP rats) were compared to wild type (WT) littermates that express non‐amyloidogenic rodent amylin (n=10 rats/group). Result: Blood amylin levels measured by ELISA were ∼2‐fold higher in 16‐month old HIP rats compared to WT littermates (P<0.01). The Thiovlavin T (Th T) fluorescence signal intensity in blood lysates from HIP rats increased compared to that in WT littermates indicating the presence of amyloid‐forming in the circulation in HIP rats (P<0.01). This was associated with higher amylin concentration in brain microvessel lysates (P<0.05) and amylin immunoreactivity signal intensity in brain sections. Plasma erythropoietin, a marker of systemic hypoxia was higher in HIP rats than in WT littermates (P<0.05), which correlated with brain accumulation of HIF‐2α (P<0.05) and HIF‐1α (P=0.07), and with altered mitochondrial DNA in brain tissue (P<0.05). Conclusion: Increased circulating levels of amyloid‐forming amylin promotes cerebrovascular amylin deposition leading to brain hypoxic‐ischemic injury. Future studies need to address functional effects of amylin‐induced brain hypoxia signaling in the brain.